Resting Heart Rate and In-Hospital Mortality in Acute Ischemic Stroke Patients With and Without Atrial Fibrillation - Zhang, Chunyuan; Wang, Xianhui; You, Shoujiang; Dong, Hongli; Zheng, Danni; Pei, Shaofang; Cao, Yongjun; Zhong, Chongke; Liu, Chun-Feng; Han, Qiao (Circulation Journal, 2020)
Background:The prognostic role of resting heart rate (RHR) on mortality in acute ischemic stroke (AIS) patients including atrial fibrillation (AF) is unclear. This study evaluated the relationship between RHR and in-hospital mortality among all AIS patients with and without AF.Methods and Results:The study enrolled 3,447 AIS patients from December 2013 to May 2014 across 22 hospitals in Suzhou City. Patients were divided into 2 groups based on median baseline RHR (<76 and ≥76 beats/min). Cox proportional hazard regression models were used to estimate the effects of RHR on all-cause in-hospital mortality. During hospitalization, 124 patients (3.6%) died from all causes. A multivariable model adjusted for potential covariates showed that higher RHR (≥76 beats/min) was associated with an increase in the risk of in-hospital mortality among AIS patients (hazard ratio [HR] 1.63; 95% confidence interval [CI] 1.09–2.45; P=0.018). This relationship was consistent in a subgroup analysis of patients without AF (HR 2.39; 95% CI 1.29–4.45; P=0.006). However, there was no significant association between higher RHR and in-hospital mortality among patients with AF (P=0.654). Similar findings were confirmed in analyses with heart rate as a continuous variable.Conclusions:Higher RHR at admission was independently associated with in-hospital mortality in AIS patients without AF.